2018
DOI: 10.1111/jvim.15046
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Factors for Early Seizure Recurrence in Dogs Hospitalized for Seizure Evaluation

Abstract: BackgroundEpileptic seizures are a common cause for neurological evaluations in dogs.Hypothesis/ObjectivesTo determine the timing, frequency, and risk factors for early seizure recurrence (ESR) among dogs admitted to the hospital for seizure evaluation and to facilitate rapid decision making about whether dogs should be placed in the intensive care unit (ICU) or day ward.AnimalsNine‐hundred twenty‐two dogs referred for seizure investigation; 214 patients were included.MethodsRetrospective study. Medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…These results confirm that although RSD are less frequently diagnosed in cats than in dogs, 7,8,37 RSD are a relatively common clinical presentation for cats evaluated by veterinary practitioners, which is consistent with previous reports. 38,39 Numerically, despite the relatively low prevalence of these disorders, an estimated 10.9 million cats are owned in the UK with 24% of UK adults owning a cat, 40 which equates to a substantial number of potentially affected cats in the UK. Our findings are substantially lower than the 2.1% and 3.5% prevalences of seizures previously reported in referral feline populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results confirm that although RSD are less frequently diagnosed in cats than in dogs, 7,8,37 RSD are a relatively common clinical presentation for cats evaluated by veterinary practitioners, which is consistent with previous reports. 38,39 Numerically, despite the relatively low prevalence of these disorders, an estimated 10.9 million cats are owned in the UK with 24% of UK adults owning a cat, 40 which equates to a substantial number of potentially affected cats in the UK. Our findings are substantially lower than the 2.1% and 3.5% prevalences of seizures previously reported in referral feline populations.…”
Section: Discussionmentioning
confidence: 99%
“…41 Considering the differences between cats and dogs, although the prevalence for RSD in cats is considerably lower than the prevalence in dogs with at least 1 seizure reported previously, 8 the inclusion criteria for RSD in our study required cats to have had at least 2 seizure events separated by at least 24 hours, an epilepsy diagnosis, or treatment using ASD. Given that toxicity and metabolic disturbances (reactive seizures) are responsible for many single seizure events, 3,38,39 this situation may account for a proportion of the differences reported between the species. Additionally, recognition of seizures in cats often is complicated by the heterogenous semiology of the condition in this species, 4,13,42,43 such that the true proportion of cats with RSD may be higher than that reported by owners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 sudden unexpected deaths in the present study in dogs, 7 occurred during the night and 5 during daytime. Kwiatkowska et al described that during hospitalization 50% of dogs showed another seizure event within 7 h after in house placement ( 50 ). Consequently, intensive monitoring during the clinical stay of dogs with IE, especially at night, is absolutely necessary and advisable ( 51 ).…”
Section: Discussionmentioning
confidence: 99%